2021
DOI: 10.1021/acs.bioconjchem.1c00292
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Amphiphilic-Based Supramolecular Structures with Anti-HIV-1 Activity

Abstract: In a previous work, we defined a novel HIV-1 fusion inhibitor peptide (E1P47) with a broad spectrum of activity against viruses from different clades, subtypes, and tropisms. With the aim to enhance its efficacy, in the present work we address the design and synthesis of several peptide amphiphiles (PAs) based on the E1P47 peptide sequence to target the lipid rafts of the cell membrane where the cell–cell fusion process takes place. We report the synthesis of novel PAs having a hydrophobic moiety covalently at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…[27][28][29][30][31][32] In recent decades, the variety of peptide sequences employed in PAs has been greatly expanded, [33] as well as their applications ranging from neural tissue regeneration [34] to drug delivery, [35,36] antimicrobial systems, [37] peptide vaccines, [38,39] immune-therapeutic applications [40,41] and non-viral gene delivery. [42][43][44] For instance, by attaching a fatty acid residue to antibacterial [37,45] and antiviral peptides, [46][47][48][49][50][51] their potency was greatly improved. Recent works have shown that PAs are internalized via lipidraft mediated endocytosis by a variety of cell lines without affecting cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32] In recent decades, the variety of peptide sequences employed in PAs has been greatly expanded, [33] as well as their applications ranging from neural tissue regeneration [34] to drug delivery, [35,36] antimicrobial systems, [37] peptide vaccines, [38,39] immune-therapeutic applications [40,41] and non-viral gene delivery. [42][43][44] For instance, by attaching a fatty acid residue to antibacterial [37,45] and antiviral peptides, [46][47][48][49][50][51] their potency was greatly improved. Recent works have shown that PAs are internalized via lipidraft mediated endocytosis by a variety of cell lines without affecting cell viability.…”
Section: Introductionmentioning
confidence: 99%